Letter: functional dyspepsia is associated with duodenal eosinophilia in an Australian paediatric cohort—methodological issues to avoid misinterpretation. Authors' reply. Issue 3 (4th July 2017) - Wauters, L.; Nightingale, S.; Jones, M.; Talley, N. J.; Walker, M. M.
Abstract : Linked Content This article is linked to Wauters et al, and Safiri and Ayubi papers. To view these articles visithttps://doi.org/10.1111/apt.14045 andhttps://doi.org/10.1111/apt.14158 .